Type beta transforming growth factor/growth inhibitor stimulates entry of monolayer cultures of AKR-2B cells into S phase after a prolonged prereplicative interval. - Shipley, G D (1985)
Type beta transforming growth factor/growth inhibitor (TGF-beta/GI) is demonstrated to be a potent stimulator of DNA synthesis in AKR-2B mouse embryo cells with a prolonged (greater than 24 hr) prereplicative phase when compared with other growth factors (epidermal growth factor, platelet-derived growth factor, or fibroblast growth factor) that induce DNA synthesis 12-14 hr after stimulation. In addition, TGF-beta/GI inhibits the early peak of DNA synthesis produced by EGF and insulin before the later stimulatory effects of TGF-beta/GI become manifest. TGF-beta/GI induces a marked morphologic transformation in these cells prior to their entry into S phase. Like the other growth factors, TGF-beta/GI stimulates an early increase in the rate of protein synthesis in AKR-2B cells and its stimulatory effect on DNA synthesis is enhanced by insulin. The data show that this molecule is a growth factor for certain mesenchymal cells in monolayer culture but only after a prereplicative phase that is significantly longer than that of other growth factors.